THE ROLE OF E-SPT TOWARDS INCREASING TAXPAYER COMPLIANCE WITH PERSONAL PERSONS IN REPORTING INCOME TAX (PPH) AT THE TAX SERVICE OFFICE (KPP) PRATAMA WEST MAKASSAR - Mariana, Lina (Jurnal Ekonomi Balance, 2018)
This research aims to determine an individual taxpayer compliance rate in reporting the Electronic Income Tax Notification at Pratama West Makassar Tax Service Office (KPP). The type of research is descriptive qualitative, which researcher does the analysis by describing a circumtance that occur in the field or an object in the form of word description based on information obtained from the authorities, either through interviews or data that has been given. There are three methods to gather the data which are observation, interview, and documentation.The research took two month that was started on March 2018 to May 2018. The results of the research conducted indicate that E-SPT has less role in increasing individual taxpayer compliance in reporting income tax at Pratama Makassar West Tax Service Office (KPP). From year to year, there has been a significant decline from 2015 to 2017. The level of compliance of individual taxpayers in reporting timely e-SPT PPh in 2015 amounted to 38.59%, then in 2016 the level of compliance decreased to 13 , 41% and in 2017 the level of compliance was 4.03%.